Compensation for topographic effect on P-band PolSAR data with a polarimetric decomposition technique - Yin Zhang; Ding-Feng Duan (Journal of Electronic Science and Technology)
A P-band polarimetric synthetic aperture radar (PolSAR) sensor has deep penetration ability into and through the vegetation canopies in forested environments. Thus, the sensor is of great potential to accurately assess forest parameters such as coverage, stand density, and tree height. Unfortunately, the radar backscatter from complex terrain can adversely impact the backscatter from trees or forests, and forest parameters assessed can be erroneous. Thus, reducing the topographic impact is an urgent must. In this study, a topographic compensation algorithm has been studied. To assess the algorithm's validity and effectiveness, we applied it to P-band PolSAR datasets in four forested areas in the US. Trees in the forest stands have diverse species, and the topographic conditions of the terrain differ. Significant topographic impact on the P-band PolSAR data exists before the topographic compensation algorithm. After the algorithm, the impact decreases noticeably qualitatively and quantitatively. The algorithm is valid and effective in reducing the topographic influence on the PolSAR data and, consequently, provides a better chance of retrieving accurate forest parameters.